Trend Analysis Of Financial Statements For Evaluating PT BNI Life Insurance’s Performance - Hamidah Hamidah; Hikmat Prabawa; Raudatul Medina; Irsan Herlandi Putra (Universitas Indonesia Membangun, 2024)
Financial reports can provide an overview of the company's performance in each period from year to year. The purpose of this research is to evaluate the financial performance of PT BNI Life Insurance using trend analysis techniques in the statement of financial position and income statement. The research method used in this study is a descriptive method with a quantitative approach, in which the author collects data in the form of a balance sheet financial position report. Data collection techniques used are documentation and literature study. The results of this study indicate that there are fluctuating developments in the balance sheet financial statements and profit and loss, in the balance sheet from 2017 to 2021 shows an increase in company performance, while in the income statement from 2017 there is a significant decrease in 2018 and subsequently fluctuating experienced increases and decreases in performance from 2019 to 2021 even though in 2020 and 2021 the company's performance has shown improvement. In conclusion, using trend analysis it can be predicted that the postal value of the coming year will experience the same fluctuating developments as in previous years.